Bibliometric Analysis of the Implementation of Good Governance on Community Welfare - Loso Judijanto; Rahmat Ramdhani; Rani Eka Arini (Westscience Press, 2024)
This study conducts a comprehensive bibliometric analysis of the relationship between good governance and community welfare, utilizing data from the Google Scholar database spanning the years 1981 to 2024. The analysis reveals that good governance is a central theme in the literature, closely associated with key topics such as community welfare, corporate governance, sustainable development, and economic growth. The findings underscore the importance of transparency, accountability, and citizen participation in governance reforms to enhance social and economic outcomes. Additionally, the study highlights the evolving role of corporate governance and the potential of decentralization and local governance to improve community welfare. These insights have significant practical implications for policymakers, practitioners, and researchers, emphasizing the need for an integrated approach to governance that addresses both public and private sectors while empowering local authorities. The study concludes that a holistic governance strategy is essential for achieving sustainable development and equitable community welfare.